Comparative study of mechanical and physiological gait efficiency following anterior cruciate ligament reconstruction and rehabilitation - Sweif, R. E.; Abdallah, A. A. (Medicina dello Sport, 2015)
Aim. Gait efficiency is used to evaluate energy consumption especially in patients with movement disorders. This study compared the physiological and mechanical measures of gait efficiency between patients with ACL reconstruction (ACLR) following rehabilitation and healthy controls and correlated among these measures.